Anti-Bacterial Potential of Siddha Herbo-Mineral Formulation Linga Chenduram: An In-Vitro Study - Soruban, T.; Sathiyaseelan, V. (Postgraduate Institute of Indigenous Medicine University of colombo, 2025)
Many existing antibiotics have limitations regarding their effectiveness against various pathogens and often cause adverse effects. Overuse of these antibiotics has led to the emergence of drug-resistant microorganisms. The Siddha system of medicine offers promising potential for combating these resistant pathogens. Linga Chenduram (LC), a traditional herbo-mineral preparation mentioned in the ancient Siddha text Anuboga Vaithiya Navanitham, was the focus of this study. The aim of this study was to screen the anti – bacterial potential of Siddha herbo-mineral formulation LC. Anti-bacterial activity of the sample was tested for E.coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853) and Staphylococcus aureus (ATCC 25923) to determine the diameter of inhibition zone (DIZ), minimum bactericidal concentration (MBC) and minimum inhibitory concentration (MIC). The study results demonstrate that a concentration of 1000 μg/mL of LC effectively inhibited the growth of all tested organisms. The minimum bactericidal concentration (MBC) was determined to be 250 μg/mL. At this concentration, the remaining colony counts were as follows: E. coli (285 colonies, equivalent to 14.2 x 10³ CFU/mL), Pseudomonas aeruginosa (96 colonies, equivalent to 4.8 x 10³ CFU/mL), and Staphylococcus aureus (33 colonies, equivalent to 1.65 x 10³ CFU/mL). The minimum inhibitory concentration (MIC) at which 50% of the bacteria were inhibited (MIC50) was 405.584 μg/mL, 459.61 μg/mL, and 515.575 μg/mL for E. coli, Pseudomonas aeruginosa, and Staphylococcus aureus, respectively. Based on these results, it can be concluded that Linga Chenduram (LC) exhibits promising antibacterial activity against E. coli, P. aeruginosa, and S. aureus. This suggests its potential as a natural alternative or adjunct therapy for infections caused by these pathogens
Keywords: Anti-bacterial; Anti-bacterial; Linga chenduram; Pseudomonas aeruginosa; Staphylococcus aureus